The sense of coherence and quality of life of patients after heart transplantation - Milaniak, Irena (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Background: Heart transplantation (HTX) is an effective treatment for end-stage heart failure. Quality of life after HTX is improved and the patient returns to normal activity. Defining and measuring indicators of quality of life is important in term of holistic care these group patients. Objective: Assessment of impact of sense of coherence on the quality of life (QOL) after HTX Material and methods The study population consisted of 121 patients (30 women and 91 men); aged from 18 to 77 years, mean age of patients was 55, 01 years (± 13, 23, median 58). Time after heart transplantation was from 3 months to 20 years (mean 10.54 ± 5.24, median 11).. There were used questionnaires measuring quality of life (WHOQOL-BREF), and sense of coherence(SOC-29). Results More than half of the respondents assessed the overall quality of life and satisfaction with their health status at a good or very good level. The lowest was functioning in somatic (physical) domain (average 13,035 ± 1,549) and psychological domain (mean 13,040 ± 1,100), the best functioning was evaluated in social relationships domain (mean 15,044 ± 2,404). There was a statistically significant, positive relationship between sense of coherence and quality of life. Univariate regression analysis showed that sense of coherence explains the quality of life in all domain Conclusions Sense of coherence have a significant impact on the quality of life of patients after heart transplantation.